Radiological characterization of metal oxide semiconductor field effect transistor dosimeter - Chan-Hyeong Kim; Sang-Hoon Lee; Baodong Wang; X.George Xu (Functional Materials, 2004)
This paper reports our effort to develop a detailed 3D Monte Carlo simulation model of the High-Sensitivity MOSFET dosimeter using the MCNP 4C code for radiological charac -terization. To determine the dosimeter response accurately, this study has taken three actions: (1) The absorbed dose to the sensitive volume of the dosimeter is calculated directly from electron trajectories; (2) The electrons are forced to make at least ten substeps in the sensitive volume; and (3) ITS-style energy indexing algorithm is used instead of the default MCNP-style energy indexing algorithm. Our results show that the developed model calculates the angular dependence, absorbed dose, and energy dependence of the dosimeter very satisfactorily when we compare the results with the measured values and theoretical values. В статье описана попытка разработки подробной трехмерной модели Монте-Карло для высокочувствительного дозиметра на основе полевого МОП-транзистора (MOSFET) с применением кода MCNP 4C для определения радиологических характеристик. Для точного определения отклика дозиметра при исследовании были применены три приема: 1) поглощенная доза для чувствительного объема дозиметра рассчитана непосредственно из траекторий электронов; 2) электронам приписаны, по меньшей мере, 10 энергетических ступеней в чувствительном объеме; и 3) вместо алгоритма индексации энергии, применяемого в MCNP по умолчанию, использован алгоритм индексации энергии типа ITS. Наши результаты показывают, что разработанная модель позволяет весьма удовлетворительно рассчитывать угловую зависимость, поглощенную дозу и энергетическую зависимость для дозиметра, что следует из сопоставления полученных результатов с экспериментальными и теоретическими значениями. В робот! описано спробу розробки детальної тривимірної модєлі Монте-Карло для високочутливого дозиметра на основі польового МОП-транзистора (MOSFET) з застосуванням коду MCNP 4C для визначення радіологічних характеристик. Для точного визначення відгуку транзистора при дослідженні було застосовано три прийоми: 1) поглинену дозу для чутливого об’єму дозиметра розраховано безпосередньо за траєкторіями електронів; 2) електронам приписано щонайменше 10 енергетичних ступенів у чутливому об’ємі; і 3) замість алгоритму індексації енергії, застосованого в MCNP за відсутності застережень, використано алгоритм індексації енергії типу ITS. Наші результати вказують, що розроблена модель дозволяє цілком задовільно розраховувати кутову залежність, поглинену дозу та енергетичну залежність для дозиметра, що витікає із зіставлення одержаних результатів з експериментальними та теоретичними значеннями.